O tratamento da sialorréia na clínica fonoaudiológica: articulações entre corpo e psiquismo - Pombo, Angélica de Menezes (2008)
Introduction: The indisociability between language, body and psychism is an assumed presupposition of several researches that approach the speech therapy clinic method on the treatment of many symptoms (BIRKMAN E CUNHA, 2006; MACHADO, 2007; PALLADINO, SOUZA E CUNHA, 2004). This dissertation talks specifically about the sialorrhea, which manifests itself on patients with cerebral palsy, in the interface between speech therapy and psychoanalysis, what allows to approach the body in its symbolic condition in joint with the biological one. Objective: To investigate the speech therapy clinic method in the treatment with the sialorrhea on patients with cerebral spastic palsy, from biopsychic. Method: Research innate physician-qualitative by means of two clinical cases studies. Subjects: (1) Bruno, 5,0 years old, neurological diagnosis of non-evolutive chronic encephalopathy and speech therapy complains of sialorrhea (with predominantly sensitive oral region deficit) and language acquisition retard. (2) Carlos, 14,0 years old, neurological diagnosis of nonevolutive chronic encephalopathy and speech therapy complains of sialorrhea (with predominantly oral region motor deficit) and language disturbance. Procedure: The data was collected with the clipping of the instances of the interview and the treatment, apprehended through the therapeutic experience. The clinic material was registered systematically in writting. Rules of interpretation of results: The theoretic referencial that guided the interpretation of the results was based in texts from speech therapy and psychoanalysis, with emphasis in the idea of pulsional/erogenous body. Results: The sialorrhea acquired double representation: show fails neurophysiologic that perturb the oral sensitivity and its erogenous and also imperfections on the unconscious image of the body constitution that perturb the rhythm of swallowing. Subject (1) The mouth excitation associated to the proprioceptiva technique favored the the oral region sensitization, diminishing the sialorrhea. Subject (2) The corporal image reorganization with emphasis on the oral region caused the appropriation of its corporal scheme, increasing the saliva deglutition rhythm. Conclusion: To consider the psychoanalytical body conception to approach it in the speech therapy clinic with patients that present neurological injury can help the physician therapeutical method of sialorrhea. On this dimension, the use the motor oral techniques become the entrance door to excitation the region oral, favoring the contention of saliva